A review of neonatal peripherally inserted central venous catheters in extremely or very low birthweight infants based on a 3-year clinical practice: Complication incidences and risk factors - Wu, Yaohua; Yan, Jing; Tang, Mengyan; Hu, Yanling; Wan, Xingli; Li, Xiaowen; Chen, Qiong; Li, Xia (Frontiers in Pediatrics, 2022)
Background: The application of peripherally inserted central venous catheters (PICCs) in neonates has proven effective in avoiding repetitive insertions and excessive use of transfusion consumables. However, the frequent occurrence of PICC-associated complications deserves special attention, especially in extremely or very low-birthweight (E/VLBW) infants, which in turn affects the quality of neonatal PICC practice. Therefore, we conducted a retrospective study of a three-year clinical practice of neonatal PICC in E/VLBW infants to understand the incidences of various catheter-related complications and their risk factors to help form an empirical summary and evidence-based guidance for the improvement of practice. Methods: A retrospective study was conducted based on a three-year practice of neonatal PICC in E/VLBW infants. Neonatal health records were collected, including demographic characteristics, PICC placement data, and treatment information. Results: A total of 519 E/VLBW infants were included in this study. There were 77 cases of complications involving 72 infants with an overall incidence of 12.13%. The order of incidences of different complications from high to low was phlebitis (7.71%), malposition (3.66%), leakage (1.35%), pleural effusion (1.15%), central line-associated bloodstream infections (0.58%, 0.25/1,000d), and accidental removal (0.38%). Multivariate analysis revealed that the inserted vessel was an independent risk factor for PICC-associated complications (mainly phlebitis; p=0.002). Neonatal PICCs inserted in the axillary vein were only one-tenth (p=0.026) as likely to cause phlebitis as in the basilic vein, whereas when applied in the saphenous vein, neonatal PICCs were five times as likely to cause phlebitis (p=0.000). Conclusion: E/VLBW infants might be more inclined to develop PICC-associated phlebitis. Catheters inserted in the axillary vein or the basilic vein are preferred if possible.